Factors affecting stock market return in Malaysia / Mohd Alif Darwish Ahmad Fais - Ahmad Fais, Mohd Alif Darwish (2022)
This study examines the link between the Malaysia stock market return (FTSE KLCI) and four macroeconomic factors, namely Interest Rate, Gross National Income, money supply and Gross Domestic Product during a 40-year period from 1981 to 2020. The majority of the previous research, however, are conducted in industrialised countries and large economies rather than growing markets like Malaysia. The goal of this study is to expand on previous research by looking at the influence of several macroeconomics drivers on Malaysia stock market return (FTSE KLCI), such as Interest Rate, Gross National Income, money supply and Gross Domestic Product. The assistance in the relief of the strain connected with various research orders is studied using descriptive analysis in this study. To find out if the data gathered is stationary or not, Unit Root Test is also conducted. The correlation test was also used in this study to examine the significance of the association between variables. Multiple Regression Analysis was also included to know the coefficient value, the significance of variables of Dependant and Independent of each variable. From all the test conducted, we found out that the interest rate has a significance relationship with the Stock market Return on two test which is the correlation test and Multiple Regression Test. For Gross National Income, it has significance value in correlation test but not in the regression test. Meanwhile for Money Supply, the variable doesn't have significance relationship on both correlation and Multiple Regression Test. Lastly, Gross Domestic Product also has the same result such as Gross National Income which it has significance value in correlation test but not in the regression test.